Ocular manifestations and clinical profile of multisystemic inflammatory syndrome in children during COVID-19 pandemic - Mandal, Arnab; Kumari, Ekta; Roy, Amaresh; Bandyopadhyay, Mousumi (International Journal of Research in Medical Sciences, 2021)
Background: Multisystemic inflammatory syndrome in children (MIS-C) is a new childhood disease, which is associated with Severe acute respiratory syndrome corona virus 2 (SARS-CoV-2). The objective of the study was to evaluate ocular manifestations and clinical characteristics of MIS-C during COVID-19 pandemic. Methods: A cross-sectional observational study was conducted among 48 MIS-C patients (≤19 years) at Burdwan Medical college and hospital in West Bengal, India from April 2021 to June 2021. History taking, clinical examination and necessary investigations of all the patients were done. Results: Out of 48 patients, 18 patients (37.5%) presented with conjunctivitis, 4 (8.3%) with eyelid swelling, 2 (4.2%) with episcleritis, 2 (4.2%) with papilledema, 1 (2.1%) with subconjunctival haemorrhage, 1 (2.1%) with uveitis, 1 (2.1%) with retinitis and 4 (8.3%) with decreased vision. Other clinical manifestations included fever, skin rash, loose stool, vomiting, abdominal pain, cough, peripheral oedema, myalgia, breathlessness, altered sensorium, cervical lymphadenopathy, shock, oliguria, chest discomfort and joint swelling. Serum inflammatory, coagulation and cardiac markers were deranged. Conclusions: Ocular and other clinical manifestations in MIS-C were due to post-COVID immuno-dysregulation resulting in “cytokine storm” and hyper-inflammatory response. Conjunctivitis was the most common ocular manifestation. There was a positive correlation between severity of the conjunctival hyperaemia and level of serum inflammatory markers.